Poverty profiles and nutritional outcomes of using spate irrigation in Ethiopia - Hagos, Fitsum; Mulugeta, A.; Langan, Simon J.; Lefore, Nicole; Abebe, Yenenesh (Wiley, 2017)
Development partners and public investors assume that spate irrigation reduces household poverty and malnutrition. This article examines whether the poverty profiles of smallholder farmers and the nutritional outcomes of their children have improved as a result of using spate irrigation. The study areas were in two regional states in Ethiopia. Twenty-five users each, both from traditional and modern spate irrigation schemes, and an equal number of non-users responded to a structured questionnaire. Anthropometric measures of 122 children under five were measured using a hanging scale and stadiometer. The results indicated that all poverty indices were significantly lower for the spate irrigation users compared to non-users, and were even lower for modern spate compared to traditional spate systems. Our results did not show gender differences, using sex of the household head as a crude measure of gender, in poverty profiles. Stochastic dominance tests showed that the poverty comparisons between users, traditional and modern, and non-users are statistically robust. It can be concluded that the use of spate irrigation can significantly reduce poverty, and modernizing spate systems further increases its poverty-reduction impact. However, anthropometric measures indicated that use of spate irrigation did not have significant nutritional effects, suggesting the need for nutrition-sensitive interventions, such as nutrition education and awareness and multisectoral collaboration.